Perjalanan Mas : memoir Muhammad Ariff Ahmad - Mas, 1924- (Angkatan Sasterawan '50, 2003)
Autobiography of Muhammad Ariff Ahmad, a Singaporean author and prominent personality active in Malay language, literary works, and culture in Singapore.